Per- and polyfluoroalkyl substances, genetic factors, and sleep health in reproductive-aged women: a cross-sectional study of the Shanghai Birth Cohort - Ruisi Wu; Xiaoqing He; Wen Jiang; Azhu Han; Ying Tian; Jun Zhang; Yun Huang (Environment International, 2025)
Perfluoroalkyl and polyfluoroalkyl substances (PFAS) may exert neurotoxic effects and disrupt endocrine function. However, the relationship between PFAS exposure and sleep disturbances in reproductive-aged women, and its interaction with genetic susceptibility, remains unclear. This study included 971 women from the Shanghai Birth Cohort preconception cohort. A total of 22 PFAS were measured in plasma, and sleep quality was assessed using the Pittsburgh Sleep Quality Index. Modified Poisson regression and quantile g-computation models estimated the effects of individual PFAS and PFAS mixtures on sleep disturbances. Polygenic risk scores were used to evaluate the cumulative genetic effects of sleep disturbances. 6:2Cl-PFESA was associated with increased snoring and less daytime dysfunction, though these associations did not remain significant after FDR correction. Exposure to PFAS mixtures was significantly associated with an increased risk of snoring (RR: 2.02, 95 % CI: 1.06–3.83). Significant associations between PFNA, PFDA, branched PFOS isomers, and chlorinated PFOS alternatives and increased snoring risk were observed in women with a high genetic predisposition. PFAS exposures and genetic variants showed additive effects on snoring risk, with RERI of 1.19 for PFNA, 1.06 for PFDA, 4.18 for 8: 2Cl – PFESA, 0.43 for 6: 2Cl – PFESA, 5.96 for 3 m-PFOS, 11.11 for 1 m – PFOS, and 0.40 for n-PFOS. These findings suggest PFAS exposure, particularly emerging alternatives and isomers of PFOS, may increase snoring risk in reproductive-aged women with a higher genetic predisposition.